Dependence of lunar mare microwave brightness temperature on FeO and TiO2. (1st November 2016) - Pabari, J.P.
Abstract: The Moon is known to radiate microwave emission as a grey body, depending on its surface emissivity and physical temperature. Measurement of lunar brightness temperature can reveal surface properties and thermal behavior, as it is dependent on the surficial material. To understand possible correlation and compare the results obtained from the measured data with those obtained from the theory, we have used the amount of lunar surface material (iron and titanium), measured by the lunar prospector mission, as a first quantity in the analysis. The lunar brightness temperature, measured by a microwave radiometer on Changé-1 mission, serves as the other variable in our analysis. Global maps of lunar surface materials have been generated from the lunar prospector data sets and presented in this article. A conditional coefficient, representing the correlation between microwave brightness temperature and lunar surface material has been defined, and its analysis has been carried out for the lunar Mare region. Results show that major contribution in brightness temperature comes from lunar regolith density driven component, while a small contribution is made by the lunar surface material. The correlation results disagree with the existing theoretical model used to describe the brightness temperature dependence with surface material. In this connection, a modified permittivity model is suggested for the Mare region, based on our correlation analysis. Highlights: Lunar surface material is used as the first quantity and lunar brightness serves as the second variable in our analysis. Global maps of lunar surface materials have been generated from the lunar prospector data sets. Results show major contribution in brightness from density driven component and small ( 14 %) contribution by the material. Results disagree with existing model describing dependence of brightness temperature on surface material for the Mare region. A modified permittivity model is suggested for the Mare region, based on our correlation analysis.